EFFECTS OF PRE-THEORETIC INTUITION QUIZ AND PUZZLE-BASED CRITICAL THINKING MOTIVATION STRATEGIES ON STUDENTS’ LEARNING OUTCOMES IN SELECTED ENVIRONMENT-RELATED CONCEPTS IN BIOLOGY (2013)
The traditional instructional strategy employed by most biology teachers in teaching environment-related concepts have resulted in low learning outcomes. Two strategies have been proved in literature to have exposed students to a higher thinking order needed to recognise assumptions, evaluate controversies, and scrutinise inferences in alleviating the problem of low students‘ learning outcomes in biology, but they have not been utilised in the teaching of environmental concept in biology. This study, therefore, examined the effects of Pre-Theoretic Intuition Quiz (PTI) and Puzzle-Based Learning (PBL) on students learning outcomes in selected environment-related concepts in biology.The pretest-posttest control group quasi-experimental design with 3x2x2 factorial matrix was adopted. Four hundred and fifty one SS2 students from nine purposively selected senior secondary schools in three local government areas of Oyo State were used for the study. The schools were randomly assigned to experimental (PTI and PBL) and control (MCS) groups and the treatment lasted 14 weeks. Eight instruments were used: Instructional Guides for teachers; Students‘ Environmental Achievement Test (r=0.80), Students‘ Environmental Attitude Scale (r=0.81), Students‘ Environmental Practices Scale (r=0.82), Cognitive Style Test (r=0.81) and Assessment Sheet for evaluating research assistants. Seven null hypotheses were tested at 0.05 level of significance. Data were analysed using ANCOVA and Scheffe post hoc test. Treatment had a significant main effect on students‘ achievement score (F(2,438) = 209.62; p<0.05). Pre-Theoretic intuition quiz enhanced achievement scores (x=14.30) than PBL (x=12.61) and MCS (x=8.23). Treatment had significant main effect on students‘ environmental attitude (F(2,438) = 287.32; p<0.05). Pre-Theoretic intuition quiz enhanced attitude scores ( x =64.34) than PBL ( x =57.81) and MCS ( x =48.97).Treatment also had significant main effect on students‘ environmental practices (F(2,438) = 363.48; p<0.05). Pre-Theoretic intuition quiz enhanced practices scores (x=65.34) than PBL ( x =59.18) and MCS (x=48.33).There was a significant interaction effect of cognitive style and sex on students‘ environmental attitude scores (F (1,438) = 6.61; p<0.05).The interaction effect of cognitive style and sex on students‘ environmental practices was significant (F(1,438) = 6.03; p<0.05).Female analytical students had the highest mean score ( x =58.75) while the male analytical students (x=56.51) had the least. The interaction effect of treatment, cognitive style and sex on students attitude scores was significant (F(2,438) = 3.22; p<0.05).The mean score of analytical female students (x=65.03) in Pre-Theoretic intuition quiz was better than analytical male students (x=64.31); the mean score of non-analytical female students (x=57.15) in PBL was better than non-analytical male students ( x =55.22), while the mean score of non-analytical female students (x=48.90) in MCS was better than analytical male students (x=48.07). Pre-theoretic intuition quiz and Puzzle-based learning strategies improved students‘ achievement, attitudes and practices in environment-related concepts in biology. Biology teachers and curriculum developers should adopt these two critical thinking motivation strategies for the improvement of students‘ learning outcomes in environment-related concepts in biology